Boosting Oxygen Dissociation over Bimetal Sites to Facilitate Oxygen Reduction Activity of Zinc‐Air Battery. (21st October 2020) - Sun, He; Wang, Mengfan; Zhang, Shenghui; Liu, Sisi; Shen, Xiaowei; Qian, Tao; Niu, Xiaobin; Xiong, Jie; Yan, Chenglin
Abstract: Zinc‐air battery is of great interest but its wide‐ranging application is impeded by the sluggish cathodic reactions, especially the oxygen reduction reaction. Despite blooming development in the past decades, achieving further breakthroughs in the activity improvement still appears challenging. Herein, the critical role of bimetal sites in boosting oxygen reduction activity is identified with the combination of theoretical calculations and electrochemical experiments. Density functional theory calculations suggest the elongation of OO bond over the dual‐atom system, which is beneficial to its following dissociation and thus enhances the efficiency of the reaction. The proof‐of‐concept electrocatalyst experimentally delivers a half‐wave potential of 0.92 V versus reversible hydrogen electrode and kinetic current density of 51.9 mA cm −2, significantly outperforming the commercial Pt/C. Both aqueous and all‐solid‐state zinc‐air battery assembled with such catalyst demonstrate superior durability with little performance fluctuation, confirming their potential feasibility in the practical applications. Abstract : The critical role of bimetal FeCu sites in boosting oxygen dissociation and facilitating oxygen reduction activity are identified using theoretical calculations. The proof‐of‐concept electrocatalyst experimentally delivers excellent ORR activity with an outstanding half‐wave potential of 0.92 V, significantly outperforming the commercial Pt/C. The zinc‐air battery assembled with such catalyst illustrates superior durability, with little performance fluctuation displayed.